Вы находитесь на странице: 1из 34

1

-
(
).



+ (u ) + u = 0


t


u


+ (u ) u + p =
t
e + (u ) e + p u = q





t

p = RT , R = R/M, R = 8314 /(K).


ui u j 2 uk
 
i j = + i j , () 0.
x j xi 3 xk
C1T 3/2
() : = (T ), =
C2 + T
1

e = cvT = RT /( 1), = c p/cv = const.

ui ui u j 2 uk 2
 
= i j = + i j
x j 2 x j xi 3 xk

q = kT , k = c p/ Pr, Pr = const.

C1 = 1, 458 106 /(1/2), C2 = 110, 4 , = 1, 4, Pr = 0, 72.


1


Q (Fx Fvx) (Fy Fvy) (Fz Fvz)
+ + + =0
t x y z

u v w

u u2 + p uv uw

Q = v , Fx = uv , Fy = v + p , Fz = vw
2

w uw vw w2 + p


E (E + p)u (E + p)v (E + p)w

0

ix 
u 2
+ v 2
+ w 2

Fvi = iy , E = e + .

2
iz


(E + p)ui + i j u j qi



Z I
Q dV + (Fi Fvi) ni dS = 0
t
V S
1




+ ( u) = 0


t


u


+ ( uu + pI) = 0
t
E + (E + p)u = 0




t

-
u = 0



u

1

+ (u ) u + p = 2u
t
T + (u ) T = 2T, = k/ c p




t
1


,
.

utt = c2 2u
ut + aux = 0

( ) ut + uux = 0

:
(. )




1



ut + f (u)x = 0, u(0, x) = (x), < x < , t > 0.
: f (u) = au ,
f (u) = u2/2 .

f x,
ut + a(u) ux = 0, a(u) = f 0(u).

x = a x = b,
d
Z b
u(x,t) dx = f (u(t, a)) f (u(t, b)).
dt a

: u(x,t) = (x at)
u u u dx u du dx
+a = + = = 0, = a.
t x t dt x dt dt
1


x t ,
dx(t)/dt = a(u(t, x(t)).

u(t, x) , .
du(t, x(t)) dx(t)
= ut + ux = ut + a(u) ux = 0.
dt dt

u = (x a(u) t).
.
a 0
ut = (a tut a )
0 0
ut =
1 + 0 a 0t
0
ux = (1 tux a )
0 0
ux =
1 + 0 a0 t

, , , (1 + 0a0t) ?
1



ut + (u2/2)x = 0, u(0, x) = sin(x), < x < , t > 0.

a(u) = u. x = /2
u = 1, x = 3 /2 u = 1.

???

u=1 u = -1 x
1


1 1 1

0.8 0.8 0.8

0.6 0.6 0.6

0.4 0.4 0.4

0.2 0.2 0.2

0 0 0

-0.2 -0.2 -0.2

-0.4 -0.4 -0.4

-0.6 -0.6 -0.6

-0.8 -0.8 -0.8

-1 -1 -1
0 50 100 150 200 250 300 0 50 100 150 200 250 300 0 50 100 150 200 250 300

t =0 t = 0, 1 t = 0, 5

(x) , 0 (x) - ,

1
T=
min 0 (x)
1


,
,
Z t2 Z b
(ut + fx) = 0
t1 a
t1, t2, a, b.
, , (x,t) C0(R R+)
.

u(x,t),

Z Z Z
t u + x f (u) dxdt + (0, x) (x) dx = 0,
0

C0. ,
(x,t) (
) (x,t).
1

, ,
,

(1) ut + (u2/2)x = 0 (2) (u2/2)t + (u3/3)x = 0 ut + uux = 0.

.
1

-
, s.
x(t), u uL, uR.

d
Z b
u(x,t) dx = f (u(t, a)) f (u(t, b))
dt a


Z x(t) Z b 
d
u(x,t) dx + u(x,t) dx = f (u(t, a)) f (u(t, b)).
dt a x(t)

Z x(t) Z b
ut dx + u(t, x(t) ) x (t) +
0
ut dx u(t, x(t) + ) x0(t) = f (u(t, a)) f (u(t, b)).
a x(t)

ut = f x ,
1

f (u(t, a)) f (u(t, x(t) )) + u(t, x(t) ) x0 (t) +


f (u(t, x(t) + )) f (u(t, b)) u(t, x(t) + ) x0 (t) = f (u(t, a)) f (u(t, b)).


s(uL) uR) = f (uL) f (uR) .

fL fR u2L /2 u2R/2 uL + uR
s= = = .
uL u R uL u R 2
1


1.

0, x < 0
ut + (u2/2)x = 0, < x < , t > 0, u(x, 0) =
1, x > 0

:

 0, x < 0
0, x < t/2
u1(x,t) = u2(x,t) = x/t, 0 x t
1, x > t/2
1 x>t


s = 1/2. u1
:


.
""
x u2.
1


2.

1, x < 0
ut + (u2/2)x = 0, < x < , t > 0, u(x, 0) =
0, x > 0


1, x < t/2
u(x,t) =
0, x > t/2


s = 1/2.



.

x
1


, f (u) : f 00 (u) > 0. uL
uR ,

f 0(uL ) > s > f 0(uR).

f (u)

, .
f (u) ,
:

f(u)

f (uL) f (u) f (uR) f (uL)


u [uL , uR] [uR, uL]
uL u uR u L

ur ul u
1

.
,
.

ut + f (u)x = uxx , > 0.

0
( ).
E(u) (E 00 (u) > 0) ( ).
E 0 (u):

E 0 (u) ut + E 0(u) f (u)x = E 0(u) uxx E(u)t + F(u)x = E 0(u) uxx , F 0(u) = E 0(u) f 0(u)

E(u)xx = [E 0(u) ux ]x = E 00 (u) (ux)2 + E 0(u) uxx ,

E(u)t + F(u)x = [E(u)xx E 00(u) (ux)2] E(u)xx


d R
0, E(u)t + F(u)x 0 . , Edx 0.
dt
1


n
Ut + A Ux + B = 0, ()

u1 b1 a11 a1n
U = ... , B = ... , A = ... ... ... , a = a (x,t, u , . . . , u ), b = b (x,t, u , . . . , u )
ij ij 1 n i i 1 n
un bn an1 ann

, ai j = ai j (x,t), bi = bi(x,t),
, ai j = const, bi = const.
Ut + F(U)x = 0 .
Ut + F(U)x = 0 Ut + A Ux = 0, A = F/ U .
: Ar = r. i, det(A I) = 0,
, ri .
, lT A = lT , li.
. (*) (x,t), A
n 1, . . ., n n
ri. ,
i .
1


u 0

Wt + A Wx = 0, W = u , A = 0 u 1/ .
p 0 p u

.
det(A I) = (u )3 (u ) p/ = 0
1 = u a, 2 = u, 3 = u + a, a = p/ .
p



1 1 1
E + p u2 p
r1 = u a , r 2 = u , r 3 = u + a , H= + .
2 ( 1)
H ua u2/2 H + ua
1

       
u1 0 1 u1 0 2, x < 0
ut + A ux = 0 : + = , u1(x, 0) = 0, u2(x, 0) =
u2 t 1 0 u2 0 0, x 0

       
1 1 1 1 1 0
1 = 1, r1 = , 2 = 1, r2 = , R= , = R1 AR = .
1 1 1 1 0 1
     
w1 u 1 u + u
w = R1u, = R1 1 = 1 2
,
w2 u2 2 u1 u 2

R1 ut + R1AR = 0, wt + wx = 0 w1t + 1w1x = 0, w2t + 2w2x = 0.


 
1, x < 0 1, x < 0
wk = w0k (x kt), w01 = w1(x, 0) = , w02 = w2(x, 0) = .
0, x 0 0, x 0
1


 
1, x t < 0 1, x + t < 0
w1(x,t) = , w2(x,t) = .
0, x t 0 0, x + t 0

0, x < t 2, x < t
u1(x,t) = 1, t x t , u2(x,t) = 1, t x t .
0, x t 0, x t

1

u z

0 0

x x
v w

x x

1

u z

0 0

x x
v w

x x

1


( ).

uL , x < 0
ut + A ux = 0, u(x, 0) =
uR , x > 0
n
u(x,t) = v0k (x kt) rk
k=1

vkL , x < 0
v0k (x) =
vkR x > 0

1 < 2 . . . < n.
q n q
u(x,t) = vkRrk + vkL rk = uL + (vkR vkL) rk , q < x/t < q+1
k=1 k=q+1 k=1
1

u1 u2 q
uq = uL + (vkR vkL) rk
k=1
u3
u0 = u L , un = uR

uL
uR
x
1


ut + f(u)x = 0, A = f/ u

1(u) < 2(u) < . . . < n(u),


r1(u), r2(u), . . ., rn(u).

f 00 (u) 6= 0 :
k- ,
rTr uk (u) 6= 0 u.

f 00(u) = 0.

k- ,
rTr uk (u) = 0 u.
a a
 
ua = , . . ., .
u1 un

1) 2) 3)
1


k .
k- , -

s(uL uR) = f(uL) f(uR),


k (uL ) > s > k (uR), k1(uL) < s < k+1(uR)

uR, uL k-

uR = u(p), p0 p 0, uR(0) = uL .

s0(p)(uL uR) s(p)u0R(p) = f/ u(u) u0R(p)

A(uL) u0R(0) = s(0)u0R(0) u0R(0) = c rk (uL), s(0) = k (uL )


1


u(x,t) = b(x/t) = b( ).

x 0 1
2
b + A(b) b0 = 0 (A(b) ) b0 = 0.
t t
:
= (b( )) b0 = cr(b).
, , , c = 1.
uL

b0( ) = r(b( )), 0 0 + p, 0 = b(0)).

uR = b(0 + p) uL = b(0) k-
.
1

t u1

x x
1


, k- , u L
, uR = u(p), p0 p p0
p 0 p 0.

u2

2-S
uL 1-S

1-R
2-R

u1
1


k- w(u1, . . . , un), rTk uw = 0.
(n 1) k- .
n
rTk u = ri(u) v = v(u)
i=1 ui

, w1(v) = v2, . . . , wn1(v) = vn. wi, i =
v1
wi
1, . . . , n 1 = 0 .
v1
wi(u) .

k- k- .
u0( ) = rk (u( )). w k-
. dw/d = 0 w .

:

wi(uL) = wi(uR) i = 1, . . . , n 1.
1


du(p)
k . u(p) , = rk (u(p)).
dp
,

d k (u) du
= uk = 0.
dp dp

u(p) uL ,
s = k (uL) = k (u(p)).

dG du
G(u(p)) = f(u(p)) su(p) = (A(u(p)) s) = 0.
dp dp

f(u(p)) su(p) = const = f(uL) suL - .


.
.
ut + aux = 0 .
1



uL x < 0
ut + f(u)x = 0, u(x, 0) =
uR x > 0

2-rarefaction

1-shock u1 3-shock
u2

uR
uL
x
1

u2 t u
1-shock
1-s
uR uR
uM 2-r uL
2-s 2-rarefaction
1-r
uL uM
uM

1-s
2-r uL
2-s uR
1-r

u1 x x